2015
DOI: 10.1111/rode.12176
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Fiscal Interactions: A Spatial Analysis ofChinese Provincial Infrastructure Spending

Abstract: Using a dataset for 31 Chinese provinces from 1998 to 2006, this paper provides a spatial Durbin panel analysis to test for fiscal interactions among China's provinces in their public spending on infrastructure. We find significant positive interactions across Chinese provincial governments.Further analysis attempting to distinguish between the possible sources of such fiscal interactions reveals evidence of expenditure competition instead of yardstick competition.JEL classification: H54, H7, C23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…In the long run, a change in government health expenditure will result in a change in GDP in the opposite direction, and a drop in government expenditure will raise GDP to some extent [52,53]. This is consistent with the theory of Zong and Muysken; that is, due to the limitations on total output, there will be a dilemma between health investment and material capital investment, so health investment may have a crowding-out effect on economic growth, leading to negative and uncertain impacts [54]. The influence coefficients of positive (β + SSE ) and negative (β − SSE ) changes in social service expenditure are 5.76 and 4.62, respectively.…”
Section: Resultssupporting
confidence: 68%
“…In the long run, a change in government health expenditure will result in a change in GDP in the opposite direction, and a drop in government expenditure will raise GDP to some extent [52,53]. This is consistent with the theory of Zong and Muysken; that is, due to the limitations on total output, there will be a dilemma between health investment and material capital investment, so health investment may have a crowding-out effect on economic growth, leading to negative and uncertain impacts [54]. The influence coefficients of positive (β + SSE ) and negative (β − SSE ) changes in social service expenditure are 5.76 and 4.62, respectively.…”
Section: Resultssupporting
confidence: 68%
“…For examples, the neighboring provinces of Shanghai are Jiangsu and Zhejiang, and Jiangxi's neighbors are Zhejiang, Anhui, Hubei, Hunan, Fujian and Guangdong provinces. nb it is de…ned as the log A recent study by Zheng et al (2015) …nds that infrastructure spending in a province is positively correlated with infrastructure spending in its neighboring provinces. In addition, since y it is only a¤ected by b it and k it conditional on time dummies in equation (5), instruments of b it 2 and nb it have no direct e¤ect on y it .…”
Section: Caves and Frazer (2015)mentioning
confidence: 99%
“…For instance, Yu et al (2013) found that local governments reduce their own health spending in response to an increase in health spending in neighboring regions, supporting the hypothesis of positive spillover. Zheng et al (2015) showed that provincial governments tend to increase their own spending as public infrastructure spending increases in neighboring countries, suggesting a positive strategic interaction in infrastructure spending by Chinese provincial governments. Given that local governments can finance public spending on capital (physical capital or human capital) with debt, the above findings also reflect the existence of spillover effects in debt competition among local governments.…”
Section: Mechanisms Of Local Public Debt Competitionmentioning
confidence: 99%